(untitled) - Ferrell, O. C (Boston, MA Cengage Learning, 2017)
PART: 1 AN OVERVIEW OF BUSINESS ETHICS ; PART 2: ETHICAL ISSUES AND THE INSTITUTIONALIZATION OF BUSINESS ETHICS ; PART 3: THE DECISIONMAKING PROCESS ..
Keywords: Business ethics,Đạo đức kinh doanh